“Justice Futures”: Forensic Investigation and the Potential for Transformation in Eritrea - Tricia Redeker Hepner; Daniel Rezene Mekonnen (Modern Africa, 2022)
This article addresses the role of the dead and disappeared and the potential for forensic investigation of atrocities in the context of an evolving transitional justice debate and framework for Eritrea. As one possible component of transitional justice, forensic investigation represents an especially potent modality to document the physical evidence of atrocities, help establish truth and accountability, and catalyse deeper conversations about justice, reconciliation, repair, access to resources, and socio-political transformation. This discussion is especially relevant as human rights proponents continue to debate the implications of findings by the Human Rights Council that Eritrean authorities have committed or enabled crimes against humanity and whether these should culminate in a referral to the International Criminal Court.